Embolization of Bleeding Ileal Varices post Adnexal Biopsy in Liver Cirrhosis without Gastroesophageal Varices - Suhas D. Wagle; Yadav Munde; Smita Kori Vaze; Tejas Mankeshwar (Journal of Clinical Interventional Radiology ISVIR)
Bleeding ileal varices are rare in liver cirrhosis, where the gastroesophageal varices frequently accompany ectopic varices. Small bowel varices usually develop in patients with a history of abdominal surgery. We report a case of bleeding ileal varices without accompanying gastroesophageal varices, managed by percutaneous embolization, in a case of liver cirrhosis with no history of laparotomy. Computed tomography–guided percutaneous adnexal biopsy had been undertaken a year before the onset of bleeding.